Raising adolescents in the family - Slavković, Ana R. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2023)
The aim of this paper is to explain the characteristics of a family with adolescent member, what distinguishes it from the previous developmental stage of the family, as well as what model of upbringing facilitates and what model complicates the development of adolescents and their entry into theworld of adults. The author explains what is the key to the proper upbringing of adolescents in the family, what are the obstacles along the way, what characteristics of the family offer the best opportunities for the adolescent for proper development. The relationship between parent and child in early development is a model of later close emotional relationships, by which the child forms an image of himself and the world, learns how to modulate emotions, how to cope with the demands of the environment. Based on the results of the research, the author concludes that even in adolescence, parents remain significantly more important in relation to the peer group, if the relationship between adolescents and parents is close. The author concludes that the general well-being of adolescents requires close emotional relationships with both parents and peers, and the absence of any of these two socialization factors can significantly hinder the proper development of adolescents. The two key words that define good parenting and proper adolescent upbringing are an adequate balance between support and independence.
Keywords: Adolescence; Family; Rasing adolescents